WAYS TO INCREASE THE EFFICIENCY OF PRODUCTION RESOURCE UTILIZATION IN MINING ENTERPRISES - Abirova , Nargizabonu (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The thesis analyzes ways to improve the efficient use of production resources in mining enterprises. Rational use of mineral, technical, energy, water, labor, information and capital resources is considered an important factor in increasing enterprise efficiency. The study also highlights technological modernization, digital monitoring, energy saving, waste recycling and human capital development as key directions.